2009
DOI: 10.1155/2009/348916
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Oxoplatin: An Oral Platinum(IV) Anticancer Agent

Abstract: Platinum(IV) compounds like oxoplatin (cis, cis, trans-diammine-dichlorido-dihydroxido-platinum(IV))show increased stability and therefore can be applied orally. In a panel of 38 human cancer cell lines this drug induced S-phase arrest and cell death with IC 50 values 2.5-fold higher than cisplatin. Oxoplatin may be converted to cisplatin by intracellular reducing agents, however, exposure to 0.1 M HCl mimicking gastric acid yielded cis-diammine-tetrachlorido-platinum(IV) exhibiting twofold increased activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 34 publications
0
46
0
Order By: Relevance
“…Cell cycle arrest induced by titanocene C is clearly distinct from that of platinum-based drugs, which points to different mechanisms of action [17]. Our present findings identify expression of helicases such as topoisomerase I, IIα and MCM4 as main targets of titanocene C leading to cell cycle arrest and downregulation of HIST1H4 core histones.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Cell cycle arrest induced by titanocene C is clearly distinct from that of platinum-based drugs, which points to different mechanisms of action [17]. Our present findings identify expression of helicases such as topoisomerase I, IIα and MCM4 as main targets of titanocene C leading to cell cycle arrest and downregulation of HIST1H4 core histones.…”
Section: Discussionmentioning
confidence: 55%
“…Thus, in the present study, NCI-H526 cells were treated with titanocene C, and alterations in gene expression were analyzed using a human gene survey microarray system. Although these data need to be confirmed by PCR and/or immunochemistry, they provide an insight into the cellular pathways affected by the test compound [17]. Treatment of NCI-H526 cells resulted in significant changes in gene expression, affecting a host of transcripts involved in different cellular pathways.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, despite enormous promise and anticancer activity reported to date, none of the HSP90 inhibitors in development has been approved for cancer therapy [12]. Since platinum-based combinations are frequently used for the treatment of metastatic gastric cancer we tested cisplatin and a platinum (IV) derivative, namely oxoplatin, in combination with ganetespib for cytotoxic activity against the gastric cancer cell lines and normal IEC6 cells [9]. Combinational treatment of ganetespib with platinum substances, cis-/oxoplatin, resulted in a marked synergistic cytotoxic effect, except for the normal intestinal epithelial cell lines IEC6.…”
Section: Mkn1mentioning
confidence: 99%
“…d,l-1,2-Diamino-cyclohexane-tetrachloro-Pt(IV) has been reported that the reduction mechanism is as follows: the Pt(IV) complex binds to guanine base in DNA and subsequently induces direct-electron transfer between Pt(IV) and guanine base, in which oxidized guanine was observed [19][20][21]. In addition, several researchers have reported that the reduction of Pt(IV) compounds can be accomplished by intracellular reductants such as ascorbic acid (AsA) or thiol-containing species like glutathione (GSH), cysteine and metallothioneins [2,[22][23][24][25]. However, the mechanisms of Pt(IV) reduction and reactivity with DNA in the presence of reductants have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%